2018
DOI: 10.1016/j.jid.2017.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Alterations in Primary Acral Melanoma and Acral Melanocytic Nevus in Korea: Common Mutated Genes Show Distinct Cytomorphological Features

Abstract: Acral melanoma occurring on the palms, soles, and nails is the most common subtype of cutaneous melanoma in Asians. Genetic alterations in acral melanoma and acral melanocytic nevus are not well known. We performed next-generation sequencing and evaluated the correlations between genetic information and the clinicopathologic characteristics from 85 Korean patients with acral melanocytic neoplasms. Of the 64 patients with acral melanoma, most had lesions at the T2 stage or higher, and the heel was the most comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
2
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 35 publications
4
57
2
2
Order By: Relevance
“…Likewise, our study identified two NRAS mutant cases that arose within congenital nevi, consistent with the results of a previous study by Lu and collegues . Interestingly, our study identified two NF1 mutant AYA melanomas, genotypes not previously described in AYA melanoma and which are rarely found in nevi . Both cases arose on high UVR exposed sites, with the wide excision specimen of one case displaying an extraordinarily high degree of solar elastosis for such a young patient.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Likewise, our study identified two NRAS mutant cases that arose within congenital nevi, consistent with the results of a previous study by Lu and collegues . Interestingly, our study identified two NF1 mutant AYA melanomas, genotypes not previously described in AYA melanoma and which are rarely found in nevi . Both cases arose on high UVR exposed sites, with the wide excision specimen of one case displaying an extraordinarily high degree of solar elastosis for such a young patient.…”
Section: Discussionmentioning
confidence: 82%
“…11 Interestingly, our study identified two NF1 mutant AYA melanomas, genotypes not previously described in AYA melanoma and which are rarely found in nevi. 32,33 Both cases arose on high UVR exposed sites, with the wide excision specimen of one case displaying an extraordinarily high degree of solar elastosis for such a young patient. Therefore, the unusual presence of the somatic NF1 mutation, typically seen in much older sundamaged adults, 34 could have arisen in these AYA through increased sensitivity to UVR induced DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…By undertaking unsupervised hierarchical clustering of gene expression profiles, Jönsson and collaborators were able to categorise melanomas into four biologically relevant subgroups; MITFlow/proliferative, high-immune response, MITF-high/ pigmentation and normal-like [19]. Importantly, the MITF-low/proliferative subtype, characterised by an absence of the expression of immune-response genes, had only BRAF/NRAS-mutated samples and more ∼5-10% [3,4] rarely seen [13,43] ∼3-36% [44,46,47,52] ∼11% [53] ∼7-25% [3,51,54] GNAQ ∼1.5-2.1% [3,55] rarely seen [13,43] ∼0-17% [3,47] ∼43-57% [48,49]…”
Section: Gene Expression Profiles and Their Prognostic Implicationmentioning
confidence: 99%
“…Acral melanoma is rare in Caucasian populations, while it is the most common subtype of melanoma in Asian, African, and Latin American populations [2]. Although several genomic profiling studies of melanoma have been conducted, the numbers of acral melanoma cases in these were limited [11][12][13][14][15]. Furthermore, the genetic heterogeneity of acral melanoma has not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%